2022
DOI: 10.3390/educsci12070465
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Promoting Self-Regulation for Equity and Quality of Online Learning: New Evidence from a Multi-Institutional Survey during COVID-19

Abstract: Self-regulation is a core concept to understand the metacognitive, motivational, and emotional aspects of learning. The outbreak of COVID-19 resulted in large numbers of courses being shifted online, thus providing a large-scale setting to collect new empirical evidence to shed light on the specific challenges that different learner subgroups struggle with in the authentic online learning environment and then to provide practical implications to improve the learning outcomes by promoting learners’ online self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In simple terms, self-regulated learning (SRL) is the learners' ability to monitor and reflect on the learning process through affective, cognitive, metacognitive, motivational, and behavioral processes for themselves so that they are able to achieve learning goals (Guo et al, 2022;Umamah & Cahyono, 2020;Zimmerman, 2000). The use of SRL in writing skills is better known as self-regulated writing strategies (SRW) (Arianto & Wulyani, 2022;Umamah & Cahyono, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In simple terms, self-regulated learning (SRL) is the learners' ability to monitor and reflect on the learning process through affective, cognitive, metacognitive, motivational, and behavioral processes for themselves so that they are able to achieve learning goals (Guo et al, 2022;Umamah & Cahyono, 2020;Zimmerman, 2000). The use of SRL in writing skills is better known as self-regulated writing strategies (SRW) (Arianto & Wulyani, 2022;Umamah & Cahyono, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As online learning has become increasingly popular in recent years, research on the importance of SRL in online learning has correspondingly increased. Based on the SRL model in the general domain, studies in online learning have found that the core components of SRL, including cognitive, metacognitive, and motivational components, are critical in the online environment as well (Broadbent & Poon, 2015 ; Guo et al, 2022 ; Lee & Tsai, 2011 ; Lin et al, 2017 ). Successful online learning also requires students to employ various self-regulatory skills, such as setting clear goals, allocating learning time, arranging a non-disturbing venue, and selecting and applying effective strategies, during the different phases of SRL (Blau & Shamir-Inbal, 2017 ; Narciss et al, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, students’ acceptance of online learning affects their willingness and actual use of this new mode of learning (Aguilera-Hermida et al, 2021 ; Venkatesh et al, 2003 ). Studies conducted during the pandemic have revealed that not all students are equipped with sufficient self-regulatory skills for online learning (Bao, 2020 ; Guo et al, 2022 ; Hong et al, 2021 ), and most of them prefer face-to-face instruction (Aguilera-Hermida, 2020 ; Aguilera-Hermida et al, 2021 ; Blizak et al, 2020 ; Marković et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To support student success and retention, Covelli (2017) recommends colleges offer online orientations and other interventions aimed at improving their use of technology for learning. Instruction to promote persistence in online courses must also guide students in areas such as time management, information literacy, study skills, and critical thinking (Guo et al, 2022;Q. Li et al, 2021).…”
Section: Persistence and Equitymentioning
confidence: 99%
“…Findings from a quantitative study conducted in a developmental math class online suggest that self-regulated learning can be promoted through peer support, contact with instructors, and the formation of a virtual community for learners to help regulate each other's learning (Cho & Heron, 2015). Other strategies to promote self-regulation and self-efficacy online involve reflective practices (Delen & Liew, 2016;Stephen & Rockinson-Szapkiw, 2021), such as goal setting and metacognitive strategies to monitor progress (Guo et al, 2022;Zimmerman, 2008). According to Cho and Kim (2013), students who set mastery goals early in academic term and employ metacognitive learning strategies are more likely to self-regulate their learning by asking for support, participating in discussions, and collaborating with others.…”
Section: Self-regulation and Self-efficacymentioning
confidence: 99%